IMPROVING DIGITAL LITERACY THROUGH CANVA TRAINING AS A LEARNING MEDIUM FOR GRADE 5 STUDENTS AT SD NEGERI 1 KENANGA - Fikriyah Fikriyah; Nezwa Laeli Ramadhani; Fauzan Hamdani (Ann Publisher, 2026)
Background. Advances in digital technology in education require students to possess digital literacy skills starting in elementary school. However, the use of digital design tools in learning has not yet been optimized. Aims. This activity aims to improve students' digital literacy by training them to use the Canva application at SD Negeri 1 Kenanga. Methods. The activity was carried out through the Student Community Service Program (PMDS) using observation, interviews, and qualitative descriptive analysis. The activity involved 14 fifth-grade students. The activity was conducted through an introduction to Canva and group practice in creating digital posters. Result. The results of the activity showed an increase in students' ability to use digital design applications from 26% to 87%, as well as an increase in their understanding of digital technology as a learning medium from 30% to 90%. In addition to improving digital literacy, this activity also encouraged students' creativity and cooperation. Implementation. Thus, Canva training is effectively implemented as a digital-based learning innovation in elementary schools.